HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN GANGGUAN SIKLUS MENSTRUASI PADA SISWI SMA HARAPAN UTAMA BATAM - Isramilda, Isramilda; Prihadianto, Dino Gagah (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Menstruation is an important part of a woman's reproductive cycle, but menstrual problems can affect the normal lives of teenagers and adult women. Menstrual disorders that occur are irregular or infrequent menstrual cycles. Menstrual cycle disorders due to imbalance of Follicle Stimulating Hormone (FSH) and Luteinezing Hormone (LH) so that estrogen and progesterone levels are not normal. Several studies addressing the problem of psychosocial risk, infertility.This type of research is an observational analytic study with a cross sectional study conducted at Harapan Utama High School in January. The sampling technique is total sampling with a total sample of 94 students. The results of the study were analyzed by Chi-square. Research Results 94 respondents, there were 10 students (55.6%) who had a high-efficiency BMI and a menstrual cycle of more than 8 students (44.4%) who had a very-good IMT recently had a menstrual cycle. Then as many as 28 students (58.3%) who had a normal BMI increased the normal menstrual cycle and as many as 20 students (41.7%) who had a normal BMI increased the menstrual cycle. In addition, as many as 6 students (21.4%) who had obesity-obesity BMI increased the normal menstrual cycle and as many as 22 students (78.6%) who had obesity-BMI increased obesity. Chi-square test results obtained p = 0.006 (pâ‰¤0.05).Based on this study, there is a relationship between Body Mass Index (BMI) and Menstrual Cycle Disorders in Batam Harapan Utama High School Students in 2020